Developing A Cutout Paper Doll Game Model To Improve the Talking Skills Of 5-6 Years Old Children - Esty Susilowati (International Journal of Emerging Issues in Early Childhood Education, 2020)
This study aims to: (1) produce a cutout paper doll game model to improve the speaking skills of children aged 5-6 years at Dharma Siwi Kindergarten and Bhakti Siwi Kindergarten which qualify for early childhood play models; (2) to determine the effectiveness of the cutout paper doll game model used to improve the speaking skills of children aged 5-6 years in Dharma Siwi and Bhakti Siwi Kindergarten.This study uses a Research & Development approach. This research procedure uses ADDIE development steps including: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluations. The subject of the group trial involved 19 children aged 5-6 years and 1 teacher. The subject of the field trials involved 53 children and 4 teachers. The data analysis technique used the Wilcoxon test with the help of SPSS 19.The results of this study are (1) the cutout paper doll game model to improve speaking skills of children aged 5-6 years meets the eligibility criteria based on the responses of material experts, media experts and teachers' responses put it in the Good category; (2) the cutout paper doll game model based on the effectiveness test is proven effective at improving children's speaking skills. This can be seen from the calculation results of Aasymp.Sig. (2-tailed) that is 0.000 less than <0.05 so that there is a difference in the children’s speaking ability score between the initial and the final ability after being given treatment.